Review of the monograph by N.G. Gadzhiev, S.A. Konovalenko, M.N. Trofimov, “Theoretical aspects of the formation and development of ecological economics in Russia. Moscow, Infra‐M Publ., 2022, 169 p.” - A. A. Gadzhiev (Юг России: экология, развитие, 2022)
The monograph reviewed is devoted to the place and role of ecology and environmental safety in ensuring the sustainable socio‐economic development of society. In the conditions of the obligatory transition of the economies of the leading countries of the world from an industrial type to a new form of "green economy" aimed at ensuring the preservation of ecological systems and the maximum reduction of damage to the biodiversity of ecological systems, the Russian Federation faces the task of forming a new course of socio‐economic development of society focused on the preservation of the potential of nature and ecology at a level enabling the support of the viability of society, flora and fauna in the foreseeable future and in the long term.The authors outline the role and importance of environmental safety in the system of ensuring the economic security of the state, examine the concept of the ideology of Global Commons in ensuring sustainable socio‐economic development of society, analyse the problems and prospects for the implementation of the Green Course of Russia programme, and examine special aspects of environmental audit, accounting and control, damage assessment in the field of ecology. Special attention is paid to the forecast of the dynamics of key environmental indicators for the medium term. The main directions of increasing the effectiveness of the mechanism for ensuring environmental safety in a market economy are described.